Education for Sustainable Development (ESD) in Pre-Service Teachers Education Curriculum at Pakistan: Current Status and Future Directions - Rukhsana Durrani، Samina Malik ،Nabi Bux Jumani (PJDOL, 2023)
The concept of Education for Sustainable Development (ESD) grasps attention of the world after the UN decade (2005-2014) of Education for Sustainable Development. People from all over the world realized the need of its integration on all levels of education. This study was also designed to explore the level(extent) of integration of the components of ESD in teachers training courses of elementary program of B.Ed. 4-year.And also obtained the opinion of experts about incorporating ESD in courses of B.Ed. 4-year elementary program. For this purpose, semi structured interviews of experts and alignment matrix for analysis of courses of B.Ed. 4-year program was developed, based on three key ESD components i.e. are, social & culture, economics and environment.